Месть киллера: роман / Д. Н. Петров - Петров Дмитрий Николаевич (Фолио-Пресс, 1996)
Экземпляры: аб (20210127) / Инвентарный номер: 56195 / Цена: 40.00 / Сис.шифр: Р2 / Авт.знак: П 30 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6